2019
DOI: 10.1002/ped4.12112
|View full text |Cite
|
Sign up to set email alerts
|

Implications of hepatic dysfunction in Kawasaki disease: Time‐related changes in aspartate aminotransferase, alanine aminotransferase, total bilirubin, and C‐reactive protein levels

Abstract: Importance The cause of the hepatic dysfunction that commonly accompanies Kawasaki disease (KD) remains unclear. Objective We tried to clarify the cause of the hepatic dysfunction. Methods A total of 381 consecutive patients with acute KD, who had undergone inpatient treatment with intravenous immunoglobulin until the 7th day of illness, were divided into a group of 199 patients with an alanine aminotransferase (ALT) level ≥ 40 IU/L on admission (group I), a group of 52 patients with an ALT level ≥ 40 IU/L at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In this study, not only FC levels but also T-Bil, AST, and ALT level were associated with unresponsiveness to IVIG. Previous studies have shown that these values were higher in non-responders than in responders [20,21,22]. It is remarkable that all these factors have also been incorporated into the existing refractory prediction scores, such as Osaka, Kurume, and Gumma scores [7,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, not only FC levels but also T-Bil, AST, and ALT level were associated with unresponsiveness to IVIG. Previous studies have shown that these values were higher in non-responders than in responders [20,21,22]. It is remarkable that all these factors have also been incorporated into the existing refractory prediction scores, such as Osaka, Kurume, and Gumma scores [7,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, not only FC levels but also T-Bil, AST, and ALT level were associated with unresponsiveness to IVIG. Previous studies have shown that these values were higher in non-responders than in responders [17,18,19]. It is remarkable that all these factors have also been incorporated into the existing refractory prediction scores, such as Osaka, Kurume, and Gumma scores [7,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011,American scholar Mohammed [1] conducted a retrospective analysis on KD complicated with liver damage for the rst time;this study only described the clinical characteristics and brie y analyzed the relationship between liver damage and related in ammatory indicators;The duration or outcome of hepatic impairment was not described.In 2019,Japanese scholar Tomita analyzed the datas of 381 children with KD admitted to Kobe Medical Center General Hospital from 1983 to 2001,and found that 199/381 cases (52.2%) had liver damage,among which ALT elevation was most notable.And most ALT value reached the peak 1-3 days after the disease onset,returned to normal within 15-17 days. [13]At present,most studies believe that KD complicated with liver damage is only a transient injury,and abnormal liver enzyme markers can be rapidly improved with the control of acute in ammation. [14] However,with the deepening of people's understanding and follow-up of KD,we found that it is not rare that liver damage occurs in the subacute stage and even the recovery stage of the disease.According to a report at the 2014 China Conference, [15]6.7% (13/195) of children had this condition.In our study,the incidence of liver damage after IVIG treatment of KD patients with effective IVIG treatment was 10.8%…”
Section: Discussionmentioning
confidence: 99%